Does Start-Up Fintech Affect The Profitability Ratio Of Islamic Banks? Case Studies Of Three State-Owned Islamic Banks - Herindar, Evania; Uula, Mimma Maaripatul; Aufa, Aufa (Accounting Global Journal, 2022)
The development of financial technology in the financial services sector provides benefits and conveniences, especially in the banking services sector. In overcoming this threat, the banking industry, especially Islamic banking, initiated a strategy by collaborating with financial technology. As banks controlled by the government, state-owned banks, namely Bank Mandiri Syariah, Bank Negara Indonesia Syariah, and Bank Rakyat Indonesia Syariah, took these steps to increase the company's profitability. This study aims to analyze the effect of Financial Technology (Fintech) on the profitability of the three banks. This research is a descriptive study with a quantitative approach by comparing the profitability ratios of banks for the 2015-2020 period that have collaborated with fintech. In this study, the data normality test and Paired T-Test were carried out to compare before and after seeing fintech start-ups. The results showed that based on the analysis of ROA, ROE, BOPO, and NPM at three banks, it was found that there was no significant difference after pressure with fintech.